Logistic analysis of algae cultivation. (March 2015) - Slegers, P.M.; Leduc, S.; Wijffels, R.H.; van Straten, G.; van Boxtel, A.J.B.
Highlights: A method for quantitative analysis of algae cultivation supply logistics is developed. Transport energy consumption has been quantified for 3 regions and 2 algae species. Energy for transport is a small proportion of the energy contained in produced algae. Large supply distances are feasible without significantly affecting the energy share. Site allocation is mainly affected by resource distribution and availability. Abstract: Energy requirements for resource transport of algae cultivation are unknown. This work describes the quantitative analysis of energy requirements for water and CO2 transport. Algae cultivation models were combined with the quantitative logistic decision model 'BeWhere' for the regions Benelux (Northwest Europe), southern France and Sahara. For photobioreactors, the energy consumed for transport of water and CO2 turns out to be a small percentage of the energy contained in the algae biomass (0.1–3.6%). For raceway ponds the share for transport is higher (0.7–38.5%). The energy consumption for transport is the lowest in the Benelux due to good availability of both water and CO2 . Analysing transport logistics is still important, despite the low energy consumption for transport. The results demonstrate that resource requirements, resource distribution and availability and transport networks have a profound effect on the location choices for algae cultivation.